2017
DOI: 10.1039/c6ra27309b
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic modification of GaSe monolayer by absorption of single Fe atom

Abstract: Fe adsorbed GaSe monolayers are studied systematically using density functional theory. A strong orbit coupling effect between Fe and the vicinal Ga and Se atoms results in a half-metallicity with a 100% spin polarization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…ΔE = 55. 25 meV, showing that a 2D Cr 2 Ge 2 Te 6 has a higher energy per unit cell in AFM than in the FM state, which is more stable than in the AFM state. In addition, the literature [46] reported that the magnetic properties of Cr 2 Ge 2 Te 6 are mainly derived from the local magnetic moments on the Cr atomic sites; therefore.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ΔE = 55. 25 meV, showing that a 2D Cr 2 Ge 2 Te 6 has a higher energy per unit cell in AFM than in the FM state, which is more stable than in the AFM state. In addition, the literature [46] reported that the magnetic properties of Cr 2 Ge 2 Te 6 are mainly derived from the local magnetic moments on the Cr atomic sites; therefore.…”
Section: Resultsmentioning
confidence: 99%
“…The adsorption of transition metal atoms on the surface of black phosphorus also effectively modulates its electronic and magnetic properties [24]. It was reported that a strong orbital coupling between GaSe monolayer and transition metals was found to produce 100% spin-polarized currents [25]. A recent study also found that monolayer Cr 2 Ge 2 Te 6 nanosheet interacted with alkali metals, enhancing their ferromagnetism and exhibiting half-metallic properties [26].…”
Section: Introductionmentioning
confidence: 99%
“…Concurrently, Li et al synthesized ultrathin 2D GaSe via CVT in a tube furnace system, which showed high photoresponse and field-effect transistor (FET) characteristics [145]. The magnetic behavior of GaSe has been reported many times in theoretical studies [146][147][148][149]. The 2D unit cell of a GaSe monolayer is composed of two Ga atoms and two Se atoms.…”
Section: Gase and Gesementioning
confidence: 99%
“…Soon afterward, Lu et al systematically investigated the structural and electronic properties of Fe-adsorbed monolayer GaSe using first-principles DFT calculations. Attributed to the transfer of Fe-3d electrons, magnetic moments of −0.004 µB and −0.178 µB were induced for the nearest neighbor Ga and Se atoms, respectively, which showed antiferromagnetic coupling with the adsorbed Fe atom [147]. Similarly, Tang et al systematically studied the modulation of an electric field on the structural, electronic, and magnetic properties of a vacancy-doped GaSe monolayer using first-principles DFT calculations.…”
Section: Gase and Gesementioning
confidence: 99%
“…Due to the reduced structural symmetry, 2D materials are generally sensitive to external conditions, which opens up considerable possibilities for modulating the properties and designing functional nanodevices for monolayer GaGeTe [15]. Strain engineering [16], surface decoration [17], and nonequilibrium doping [18,19] are known as common control means; however, they will either bring in structural deformation or cause additional lattice damage which distinctively reduce the carrier mobility in the material. Magnetic field is a feasible method, but it is incompatible with global electronic and optoelectronic devices [20], Alternatively, external electric field can be a preferred option with great necessity and essential promise [21], achieving an all-electrical modification of the electronic and spintronic properties of monolayer GaGeTe will provide further avenues for novel electronic, optoelectronics and spintronics.…”
Section: Introductionmentioning
confidence: 99%